Profiling company-generic production capabilities in the process industries and strategic implications. Issue 5 (6th June 2016) - Samuelsson, Peter; Storm, Per; Lager, Thomas
Abstract : Purpose: – A robust description of the material transformation system is fundamental for understanding its capabilities and thus for communicating, prioritising and changing the system. Deploying a previously developed configuration model the purpose of this paper is to test the industrial usability of the model as an instrument to gain a better understanding of the material transformation system through externalising the generic production capabilities of the system. Design/methodology/approach: – In a multiple case study approach and using a prior conceptual configuration model of the material transformation system in the process industries as a research instrument, company-generic production capabilities were investigated in three companies representing the mineral, food and steel industries. Findings: – The empirical results supported the utility of the model as an instrument in providing a coherent set of elements that define operations and thus serve as a platform to model company-generic production capabilities and serve as input to strategizing though implicating needed change to the material transformation system. The theoretical contribution was mainly the empirical validation of the previously developed conceptual model as a tool in knowledge formation of the capabilities of the system and to outline the concept of "production capabilities configuration". Research limitations/implications: – Three sectors of the process industries were studied but it is recommended that the results should be replicated in complementary case studies or a survey of larger samples from the process industries. Those studies should not only be limited to increase the empirical knowledge base, but possibly to identify additional new variables, further refine the set of variables in the present model and investigate their relationships. Practical implications: – It is argued that the model can already be used as a tool to support both horizontal and vertical communication on production capabilities, thus facilitating, e.g. manufacturing strategy development. Originality/value: – The validated conceptual model supported by the empirical evidence is new knowledge to be used in the analysis of company-generic production capabilities in the process industries.